Combing Transcriptomes for Secrets of Deep-Sea Survival: Environmental Diversity Drives Patterns of Protein Evolution - Winnikoff, J R (Integr Comp Biol, 2019)
Ctenophores, also known as comb jellies, live across extremely broad ranges of temperature and hydrostatic pressure in the ocean. Because various ctenophore lineages adapted independently to similar environmental conditions, Phylum Ctenophora is an ideal system for the study of protein adaptation to extreme environments in a comparative framework. We present such a study here, using a phylogenetically-informed method to compare sequences of four essential metabolic enzymes across gradients of habitat depth and temperature. This method predicts convergent adaptation to these environmental parameters at the amino acid level, providing a novel view of protein adaptation to extreme environments and demonstrating the power and relevance of phylogenetic comparison applied to multi-species transcriptomic datasets from early-diverging metazoa. Across all four enzymes analyzed, 46 amino acid sites were associated with depth-adaptation, 59 with temperature-adaptation, and 56 with both. Sites predicted to be depth- and temperature-adaptive occurred consistently near Rossmann fold cofactor binding motifs and disproportionately in solvent-exposed regions of the protein. These results suggest that the hydrophobic effect and ligand binding may mediate efficient enzyme function at different hydrostatic pressures and temperatures. Using predicted adaptive site maps, such mechanistic hypotheses can now be tested via mutagenesis.